Pro-neurotensin depends on renal function and is related to all-cause mortality in chronic kidney disease. - Tonjes, A.; Hoffmann, A.; Kralisch, S.; Qureshi, A. R.; Kloting, N.; Scholz, M.; Schleinitz, D.; Bachmann, A.; Kratzsch, J.; Nowicki, M.; Paeschke, S.; Wirkner, K.; et al. (Eur J Endocrinol, 2020)
BACKGROUND: Patients with chronic kidney disease (CKD) have a high risk of premature cardiovascular diseases (CVD) and show increased mortality. Pro-neurotensin (Pro-NT) was associated with metabolic diseases and predicted incident CVD and mortality. However, Pro-NT regulation in CKD and its potential role linking CKD and mortality have not been investigated, so far. METHODS: In a central lab, circulating Pro-NT was quantified in three independent cohorts comprising 4715 participants (cohort 1: patients with CKD; cohort 2: general population study; and cohort 3: non-diabetic population study). Urinary Pro-NT was assessed in part of the patients from cohort 1. In a 4th independent cohort, serum Pro-NT was further related to mortality in patients with advanced CKD. Tissue-specific Nts expression was further investigated in two mouse models of diabetic CKD and compared to non-diabetic control mice. RESULTS: Pro-NT significantly increased with deteriorating renal function (P < 0.001). In meta-analysis of cohorts 1-3, Pro-NT was significantly and independently associated with estimated glomerular filtration rate (P </= 0.002). Patients in the middle/high Pro-NT tertiles at baseline had a higher all-cause mortality compared to the low Pro-NT tertile (Hazard ratio: 2.11, P = 0.046). Mice with severe diabetic CKD did not show increased Nts mRNA expression in different tissues compared to control animals. CONCLUSIONS: Circulating Pro-NT is associated with impaired renal function in independent cohorts comprising 4715 subjects and is related to all-cause mortality in patients with end-stage kidney disease. Our human and rodent data are in accordance with the hypotheses that Pro-NT is eliminated by the kidneys and could potentially contribute to increased mortality observed in patients with CKD.
Keywords: Adult; Aged; Aged, 80 and over; Animals; Cross-Sectional Studies; Female; Glomerular Filtration Rate/physiology; Humans; Kidney/metabolism/physiopathology; Longitudinal Studies; Male; Meta-Analysis as Topic; Mice; Middle Aged; Neurotensin/blood/*metabolism; Renal Insufficiency, Chronic/blood/*metabolism/*mortality/physiopathology